PERAN IOV WORLD (INTERNATIONAL ORGANIZATION OF FOLK ART) DALAM MELESTARIKAN KESENIAN RAKYAT INDONESIA (STUDI KASUS SENI TARI INDONESIA TAHUN 2012-2015) - Novita, Yosi; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the roles of IOV World (International Organization Of Folk Art) in conservation of culture in Indonesia esspecially about art of dance Indonesia in 2012-2015. Indonesia are most big country that have potenciall in culture resources likes tradition, religion, and adat istiadat. One of most culture famous from Indonesia are art of dance. Dance are one part of art that non things so society have to keep this art from globalizations.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the roles of IOV World (International Organization Of Folk Art) in conservation of culture in Indonesia. The theories applied in this research are international organization suchs as regional organization theory from Clive Archer and concept defenition from culture.The conclusion of the research that the roles of IOV World (International Organization Of Folk Art) in conservation of culture in Indonesia are the roles of IOV World (International Organization Of Folk Art) had cooperations wtih Government of Indonesia to create a regulations about conservation of national culture, the roles of IOV World (International Organization Of Folk Art) have participations in event of international art and culture and the roles of IOV World (International Organization Of Folk Art) create a IOV Youth and active in International Conferention about art.Key words: roles, IOV, conservation and culture.